Sistem Informasi Kepegawaian Kantor Dinas Kelautan Dan Perikanan Kabupaten Parigi Moutong - Indah Anjelina Putri; Sarintan N. Kaharu; Dewi Kusumawati Dewi Kusumawati (Sekolah Tinggi Manajemen Informatika dan Komputer (STIMIK) Bina Mulia Palu, 2025)
This research aims to build a Personnel Information System for the Marine and Fisheries Office of Parigi Moutong Regency which will facilitate the management of employee data. The types and sources of data needed in this study are primary data and secondary data. The subjects of the study are Mahriadi (Head of Program Planning, General and Personnel Subdivision), Mashening L, S.Pi (Head of P2TPI) and Iklam, S.Pi (P2TPI Staff). Data collection techniques include observation, interviews and literature. The analysis method uses a comparative method, which is a type of research that is built on two different things. The research method used is engineering research with an emphasis on software engineering using the prototype paradigm. The programming language uses PHP 5 and the database uses MySQL. The results of the research in the form of the Personnel Information System of the Marine and Fisheries Office of Parigi Moutong Regency have been completed and have been tested by the admin and can provide convenience in managing employee data efficiently. The Personnel Information System of the Marine and Fisheries Office of Parigi Moutong Regency provides access to admins and employees. Information Systems Testing uses a black box method that focuses on the functional needs of the software. The process of implementing this information system can only be accessed offline through localhost.